PENINGKATAN KEMAMPUAN MENYIMAK MENGGUNAKA METODE BERITA TELEVISI PADA PESERTA DIDIK KELAS VIII ASMP NEGERI 1 WONOMULYO KABUPATEN POLEWALI MANDAR - Sulihin Azis (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2014)
Increased listening comprehension by using the television news on VIIIA grade students of SMP Negeri 1Wonomulyo Polewali Mandar. This research based on the learners low participation in the learning of listening news, when learning takes a lot of students do not pay attention to the teacher's explanations, there are dreamy and talking to his friends so that no teacher interaction tehadap learners. As this study aims to describe the increase in the ability of listening television news VIIIA grade students of SMP Negeri 1 Wonomulyo Polewali Mandar. Jinis research used in this research is an act of class (PTK) with planning, action, observation and reflection. Subyek in this study is VIIIA grade students of SMP Negeri 1 Wonomulyo Polewali Mandar academic year 2013/2014, the number of learners as many as 32 orang.Intrumen research used in this research was the result of tests and guidelines observasi. Based on the statistics analysis conducted by researchers, the values obtained in the first cycle and the second cycle. In the first cycle the average value of learners listen to the news which is 70. And the second cycle the average value of learners listen to the news that 83.Nilai average of each cycle has increased. learners have reached a value of minimum completeness criteria as to which the expected class VIIIA SMP Negeri 1 Wonomulyo